2013
DOI: 10.1186/1477-7819-11-140
|View full text |Cite
|
Sign up to set email alerts
|

Does geography influence the treatment and outcomes of colorectal cancer? A population-based analysis

Abstract: BackgroundThe Canadian province of Manitoba covers a large geographical area but only has one major urban center, Winnipeg. We sought to determine if regional differences existed in the quality of colorectal cancer care in a publicly funded health care system.MethodsThis was a population-based historical cohort analysis of the treatment and outcomes of Manitobans diagnosed with colorectal cancer between 2004 and 2006. Administrative databases were utilized to assess quality of care using published quality indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Advanced stage, older age, emergency admission and comorbidity increased the risk of postoperative deaths following resection for CRC. Thirty‐day postoperative mortality was also higher among non‐metropolitan than metropolitan residents, which contrasts with the findings of Jorgensen et al (Australia) and Helewa et al (Canada) who found no regional disparities in 30‐day mortality, after case‐mix adjustment. International studies suggest higher volume hospitals are better placed to manage complications during surgery .…”
Section: Discussioncontrasting
confidence: 93%
“…Advanced stage, older age, emergency admission and comorbidity increased the risk of postoperative deaths following resection for CRC. Thirty‐day postoperative mortality was also higher among non‐metropolitan than metropolitan residents, which contrasts with the findings of Jorgensen et al (Australia) and Helewa et al (Canada) who found no regional disparities in 30‐day mortality, after case‐mix adjustment. International studies suggest higher volume hospitals are better placed to manage complications during surgery .…”
Section: Discussioncontrasting
confidence: 93%
“…This leads to true population-based data, irrespective of referral patterns or number of operating centers, which change over time. Investigation of geographical differences in surgical care is often based on a specific diagnosis [5][6][7][8]. To our knowledge, this issue has not been elucidated from the wider professional standpoint of upper abdominal surgery in a population-based setting.…”
Section: Countiesmentioning
confidence: 96%
“…80 Higher uninsured rates at the county level are associated with higher rates of late-stage diagnosis and mortality, and a lower likelihood of being recommended for cancer surgery. 81 A secret shopper survey of gastroenterologists in Connecticut demonstrated that only a small number of gastroenterology practices actually accepted Medicaid patients. 82 Although hospitals in California serving a high-volume of patients with CRC were found to have lower CRC death rates, minority patients were significantly less likely to use these high-volume hospitals despite a higher likelihood of living nearby.…”
Section: Health Care System Inequitiesmentioning
confidence: 99%